Technology Entrepreneurship Project (ENT 600) : Decathlon / Faisal Mohd Fouzi - Mohd Fouzi, Faisal (2021)
Technology is one of the key factors of our world’s success, yet it is also one of the most confused. As an analytical category it seems necessary for our understanding of all of humanity’s history, and indeed beyond. The use of technology in sports is growing rapidly. Wearable devices that can monitor heart rate were integrated with tracking technologies that include global positioning system (GPS), accelerometer and gyroscope sensors, which are used to describe the athletes’ movement and physical demands. Related to what am I focussing, a sauna suit is one of the technology or innovation that I have been seen. It is actually a garment made from waterproof fabric designed to make the wearer sweat profusely. A sauna suit is sometimes called a "rubber suit" because the early types were made of rubber or rubberized cloth. Now, sauna suits are typically made of PVC or coated nylon cloth. The construction is typically in the style of a waterproof sweat suit, consisting of a pullover jacket and drawstring pants. The closures at waist, neck, wrists and ankles are all elasticated to help retain body heat and moisture within the garment. In some sauna suits, the jacket also includes a hood to provide additional retention of body heat. The purpose of this case study is to identify and analysed the company based product, their problems and design solutions regarding their problems. By doing this, I can study the opportunity to exploit the markets with new advancement product to see whether the new product can be commercialized or not. Decathlon has been produced on innovation for human’s benefits which is for loss weight focussing on Decathlon Sauna Suit. However, there are some problem that can be solve and be consider for consumer satisfaction and more functionally. the Decathlon sauna suit cannot overcome the dehydration effect. In order to overcome dehydration, individual must hydrate themselves by infuse enough water to replenish back the water content within the body. So, it will suggest that add up water bank with straw infusion will encounter this problem. This is because individual will maintain body water content by infuse water directly if they feel tired or dehydrate. This intervention basically used at the hiking bag that function in the same way. After the water bank have been add up to the sauna suit, we must ensure that the ideal sport or recovery drink given to the individuals. Appropriate amount of water and specifically type of drinks can be provided inside the water bank. This is because sport or recovery drinks beneficial for individuals’ recovery to replenish excessive mineral loss inside the body. So, by providing these, recovery phase will smoothly occur without any hesitation for example injury, muscle cramps and muscle fatigue can be avoided.